Dual‐tracer PET/CT scan after injection of combined [18F]NaF and [18F]FDG outperforms MRI in the detection of myeloma lesions. Issue 2 (28th March 2019) - Withofs, Nadia; Beguin, Yves; Cousin, François; Tancredi, Tino; Simoni, Paolo; Alvarez‐Miezentseva, Victoria; De Prijck, Bernard; Hafraoui, Kaoutar; Bonnet, Christophe; Baron, Frédéric; Hustinx, Roland; Caers, Jo
Abstract: The detection rates of whole‐body combined [ 18 F]NaF/[ 18 F]FDG positron emission tomography combined with computed tomography (PET/CT), CT alone, whole‐body magnetic resonance imaging (WB‐MRI), and X‐ray were prospectively studied in patients with treatment‐requiring plasma cell disorders The detection rates of imaging techniques were compared, and focal lesions were classified according to their anatomic location. Twenty‐six out of 30 initially included patients were assessable. The number of focal lesions detected in newly diagnosed patients (n = 13) and in relapsed patients (n = 13) were 296 and 234, respectively. The detection rate of PET/CT was significantly higher than those of WB‐MRI ( P < 0.05) and CT ( P < 0.0001) both in patients with newly diagnosed and in those with relapsed multiple myeloma (MM). The X‐ray detection rate was significantly lower than those of all other techniques, while CT detected more lesions compared with WB‐MRI at diagnosis ( P = 0.025). With regard to the infiltration patters, relapsed patients presented more diffuse patterns, and more focal lesions located in the limbs compared with newly diagnosed patients. In conclusion, the detection rate of [ 18 F]NaF/[ 18 F]FDG PET/CT was significantly higher than those of CT, MRI, and X‐ray, while the detection rate of X‐rays was significantly lower than those of all other imaging techniques except for focal lesions located in the skull.